Analysis of the Implementation of Good Governance Principles in the Framework of Public Services at the One Stop Integrated Investment and Licensing Service in North Sumatra Province - Jania Fadila Aryanti; Marliyah Marliyah (Journal of Indonesian Management, 2022)
This study describes the One Stop Integrated Investment and Licensing Service Office of North Sumatra Province. The background of this research is how to apply the principles of good governance in public services and what obstacles are encountered in the application of the principles of good governance. The research was conducted at the One Stop Integrated Investment and Licensing Service, North Sumatra Province. Data was collected through interviews, observation, and recording. The resource persons in this study were not only employees, data collection and determination, but also the people who participated in licensing services. Collect, compare, and analyze data through qualitative descriptive analysis. The results showed that the application of the principles of good governance went well, especially in terms of participation, accountability, rule of law, transparency, effectiveness and efficiency, and responsiveness.